Application of Electronic Medical Record at Intensive Care Unit in Maternity and Children Hospital - Moustafa Ali Ghazi Al-Shammari (Journal of Global Pharma Technology, 2018)
Background: Electronic medical record implementation within the PICU to measure the system effectiveness with analysis the user's attitude toward the system use based on TAM3. Methods: A controlled before and after study, started from 29th Sep 2016 to 11th May 2017, were conducted in the PICU of Children Hospital. A convenience (probability) sample of pediatric patients was selected before and after EMR use. And a purposive (non-probability) sample of PICU staff was selected after 3 months of EMR application. The data were gathered from sheets in the before and after period by stopwatch and an excel spreadsheet tool. In addition to, the electronic questionnaire developed based on TAM3 by using (google forms) used to collect data from the respondent survey, for the period from (14th March - 30th April 2017). Data were analyzed using SPSS®, through applying descriptive and inferential analysis as; frequency, percentage, mean, Cronbach's alpha test, and paired-samples T test. Results: The results were the documentation time was faster using electronic recording, (10.25 min 0.38sc vs 23.9 min 0.43 sc; p < 0.001). And documentation completeness was enhanced significantly after application. All PICU users enrolling in the afterward time accomplished analyses were having highly scored of attitude toward EMR system use.  Conclusion: The EMR system implemented in the PICU overall succeed, electronic charting was faster, as well as the documentation completion recording was significantly improved. The healthcare members were having a positive attitude toward adoption of the system.Keywords: Documentation completeness, EMR, Implementation process, PICU, Technology acceptance model 3, Time.